Implementasi Teknologi Digital dalam Pendidikan: Manfaat dan Hambatan - Elisa Pitria Ningsih (EduTech Journal, 2024)
This research aims to explore the benefits and barriers in the implementation of digital technology in education. In the growing digital era, technology plays an important role in the teaching and learning process. This research uses a qualitative method with a literature study approach. Data was collected from academic databases such as PubMed, Google Scholar, Scopus, and JSTOR to search for relevant articles, books, and other scholarly sources. The results show that the implementation of digital technology brings various benefits, including increased access to information, mor e interactive learning, as well as the development of digital skills in students. Teachers reported that technology helps in presenting materials in a more engaging manner and facilitates collaborative learning. Students feel more motivated and engaged in the learning process with the use of digital devices and online learning platforms. However, the study also identified a number of barriers to the implementation of digital technology. These include limited technological infrastructure, lack of training and technical support for teachers, and disparities in access to technology between students from different economic backgrounds. In addition, some teachers expressed concerns regarding the disruption caused by the use of technology in the classroom and challenges in integrating technology with the existing curriculum. The study concludes that while digital technology has great potential to improve the quality of education, its successful implementation is highly dependent on infrastructure readiness, training for educators and appropriate strategies to address access gaps. Recommendations are provided for policy makers and education practitioners to optimize the use of digital technology to achieve better educational outcomes.